DYNAMICS OF MONEY POLITIC LAW ENFORCEMENT BY SENTRA GAKKUMDU IN THE E-MONEY ERA - Iskandar; Qolbi, Latifatul (Bawaslu Provinsi Jawa Barat, 2023)
The operation of a democratic system with the implementation of general elections to search for and elect candidates for leaders and public officials cannot be separated from the issue of criminal violations committed. The issue of support is a problem for candidates for office who run in electoral contests, both in holding elections and elections, so that many try to gain votes instantly to influence voters by providing material rewards, be it money or other materials, so that their choice is given to a particular candidate. Integrated Law Enforcement Centers which are mandated by law, both by election and election laws, to carry out handling of criminal violations often have difficulty in proving cases of money politics. Today's problems are increasingly becoming because transactions are carried out not only by carrying out conventional transactions but have entered the era of electronic transactions. The issue of limited authority is an obstacle in itself because the complexity of proof in electronic transactions cannot be easily carried out.